Vienna : The Monocle travel guide (Berlin : Gestalten, 2016)
There's much more to Austria's capital than Baroque palaces, horse-drawn carriages and the landmark venues where Mozart and Klimt first showcased their masterpieces. This guide will steer you away from the crowded Prater and its ferris wheel (although naturally we'll make a quick detour past the Vienna State Opera and Schönbrunn Palace) and out to explore the city's 23 diverse districts. We'll show you where to shop for shoes and silverware from the most venerable manufacturers and our pick of the coffeehouses for a frothy melange and slice of apfelstrudel. We'll take you to the most vibrant art galleries and toe-tapping music venues, guide you through the Museumsquartier and to our favourite brutalist buildings and also reveal the best running routes along the Danube. Vienna is a city that bridges Eastern and Western Europe with panache. It has long been the melting pot of Europe so it's easy to feel at home here as a visitor. And why wait to taste the world's best schnitzel? Pack your suitcase and let's explore.
Keywords: Reisgids; Vienna